(untitled) (Baghdad Science Journal, 2025)
This work represents implementation and investigation of optical coherent communication system between two computers. A single mode optical fiber is selected as transmission medium. The data are sent via the RS-232 standard interface with a bit rate of 9.6 kbps from personal computer (PC1) by line receive to convert the data from electrical levels (-12/+12 V) into TTL level (0/5 V). The modulation of this data was accomplished by internal modulation using laser diode type (HFCT-5208M) 1310 nm wavelength. The optical D-coupler was used to combine the optical signal that come from laser source with optical signal of laser local oscillator (OTS-304XI) at 1310/1550 nm wavelength to obtain coherent (homodyne and heterodyne) detection respectively. A PIN photodetector (HFCT-5208M) is used. Calculations of Signal to Noise Ratio (SNR) and Bit Error Rate (BER) for coherent detection were measured at different length of the optical fiber. Result show that high SNR and low BER for heterodyne detection than for homodyne detection.